Padrão espacial e dimensão humana dos espaços para prática social no Campus I da UFPB: estudo do quarteirão do conjunto humanístico - Boaventura, Flávio Brandão (2020)
This research presents a comparative analysis between the potentials of movement and permanence configured by space with real flows and experiences in the Humanistic Set (Campus I, UFPB). The identification of potential movements or permanence is structured in parameters measured in the circulations (connections among themselves); in the spaces of permanence (connections to each other) and in the visual fields depicted in the environments. The spatial configuration data is processed to establish the paths and spaces that have greater or lesser potential for circulation or permanence. For comparison, the identification of actual movements or permanence is systematized in surveys carried out in loco of passage through paths and the presence of people. The counting of people in the environments determines which paths have greater or lesser flow and which spaces have greater or lesser permanence. The study outline was the block that encompasses four (CCHLA, CE, CCSA and CEAR) of the eleven teaching centers on campus I, known as the Humanistic Complex. For understanding and characterization of the object of study, the polygonal was treated by a procedural step based on the morphological decomposition methodology presented by Coelho (2013). This step identified the paths and spaces, having a crucial character for the reliability of the parameterized data. To analyze the potential flows and encounters of the university environment, the spatial pattern was studied from the perspective of the Social Logic of Space Theory presented by Holanda (2002) and Donegan (2019). To identify real flows and encounters, pedestrian circulation and spaces of social practice were mapped using as reference the study of the human dimension in Gehl's work (2013 and 2018). The relation between real and potential flows reveals the role of the internal hierarchy, together with the important role of the link with access to the campus. The relationship between real and potential flows reveals the role of the internal hierarchy, allied to the important role of connection with campus access. The characteristics of the spaces forge a diversity of uses and users within the Humanistic Complex, creating spaces with greater socialization, prone to study, predisposed to food or tending to introspective and intimate behavior; among others. The research presents the effectiveness of morphological decomposition for mapping and classification and shows how the study of the human dimension allows identifying the use and function of Social Practice Spaces-EPS influenced by the spatial pattern, environmental comfort and the ergonomics of the furniture, and can serve as a subsidy for future interventions.